Rhabdomyolysis in Patients with Drug or Chemical Poisoning: Clinical Investigation and Implications - Fateme Eghbali; Hamid Owliaey; Soheila Shirani; Fatemeh Fatahi Asl; Reza Hosseinzadeh; Niloofar Deravi; Hamidreza Ghasemirad; Marjan Shariatpanahi; Hoorvash Farajidana (Iranian Journal of Medical Sciences)
Background: Given that poisoning patterns vary by region and no comprehensive data exist on chemical/drug-induced rhabdomyolysis in Yazd province (Iran), this investigation was conducted to assess rhabdomyolysis incidence among patients with drug or chemical poisoning.Methods: This descriptive cross-sectional study was conducted on all patients with chemical or drug poisoning in Shah Vali (Yazd) and Shahid Beheshti (Taft) Hospitals,  Iran, from March 2015 to 2020. All data were extracted from medical records. Results: Among 7800 patients with poisoning, 788 individuals (10.1%) were diagnosed with rhabdomyolysis. The predominant drug poisoning agents causing rhabdomyolysis were methadone, with 327 cases (41.5%), and benzodiazepines, with 80 cases (10.1%). The most common chemical poisoning agent was lead, occurring in 18 cases (2.28%). Acute kidney injury (AKI) requiring dialysis and death occurred in 96 (12.2%) and 55 (7%) patients, respectively. Methadone was associated with the highest frequencies of death and AKI requiring dialysis, accounting for 23 (41.8%) and 41 (42.7%) cases, respectively. A significant relationship was found between death and AKI requiring dialysis (P=0.002).  Conclusion: The frequency of rhabdomyolysis was approximately 10%, with a 7% mortality rate among affected patients. Rhabdomyolysis was more frequently associated with drug poisoning than chemical poisoning, with methadone and benzodiazepines being the most frequently causative agents. Notably, methadone poisoning was associated with significantly higher rates of both AKI requiring dialysis and mortality. Moreover, AKI necessitating dialysis was identified as a significant predictor of mortality in these patients.